THE EFFECT OF OFFSET RATIO ON OFFSET JET FLOW STRUCTURE - Rifqi Ramadhani; James Julian; Fitri Wahyuni; Riki Hendra Purba; Fathin Muhammad Madhudhu; Elvi Armadani (Universitas Muhammadiyah Metro, 2025)
Jet flow is a crucial fluid dynamic phenomenon that has been extensively studied. It is essential for various industrial applications, including surface cleaning, flow control, and cooling electronic components.Â Offset jet is an innovation in jet flow configuration that offers advantages in flow pattern control by expanding the impingement area and regulating surface pressure distribution. This study employed a Computational Fluid Dynamics (CFD) approach to investigate the influence of variations in the offset jet ratio on the aerodynamic characteristics of the flow, specifically the impingement zone area, pressure coefficient distribution, and skin friction coefficient. The standard k-Îµ turbulence model, utilizing a structured mesh and a Reynolds number of 10,000, was employed in this research. The number of mesh elements used was a fine mesh of 200,000 with an error percentage of 0.09436%. The results of the study show that an offset ratio of 3 produces the highest cf value of 0.0047 and a stable Cp distribution of 0.218, while also providing the best impingement zone area. These findings indicate that OR 3 is the most optimal configuration in terms of aerodynamics for precision system applications, with a focus on flow pattern control and wide impingement zone coverage.